Consumer Personal Data Protection in Digital Contracts: A Civil Law Review - Pipit Rahayu; Zuraidah; Otong Syuhada (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
The development of digital transactions has encouraged the widespread use of digital contracts, but on the other hand, it has raised serious issues regarding the protection of consumer data privacy. Digital contracts, which are generally in the form of standard agreements, often contain personal data protection clauses that are drafted unilaterally and place consumers in a weak position. This study aims to analyze consumer data privacy protection in digital contracts from a civil law perspective and assess the validity of privacy clauses based on the principles of contract law. The research method used is normative legal research with a legislative and conceptual approach, through a literature study of primary, secondary, and tertiary legal materials. The results of the study show that privacy clauses in digital contracts often do not reflect the principles of good faith and balance between the parties, thus potentially harming consumers. These clauses can be classified as voidable or void ab initio if they conflict with the Civil Code, the Consumer Protection Law, and the Personal Data Protection Law. This study emphasizes the importance of interpreting and drafting digital contracts that are oriented towards contractual fairness and the protection of consumer privacy rights